The specific role of childhood abuse, parental bonding, and family functioning in female adolescents with borderline personality disorder - Infurna, Maria Rita; Brunner, Romuald; Holz, Birger; Parzer, Peter; Giannone, Francesca; Reichl, Corinna; Fischer-Waldschmidt, Gloria; Resch, Franz; Kaess, Michael (Journal of personality disorders, 2019)
This study examined a broad variety of adverse childhood experiences in a consecutive sample of female adolescent inpatients with borderline personality disorder (BPD; n = 44) compared with a clinical control (CC; n = 47) group with mixed psychiatric diagnoses. BPD was diagnosed using a structured clinical interview; different dimensions of childhood adversity were assessed using the Childhood Experiences of Care and Abuse Questionnaire, the Parental Bonding Instrument, and the Family Assessment Device. A history of childhood adversity was significantly more common in patients with BPD than in the CC group. Using a multivariate model, sexual abuse (OR = 13.8), general family functioning (OR = 8.9), and low maternal care (OR = 7.6) were specific and independent predictors of adolescent BPD. The results increase our knowledge of the specific role of different dimensions of childhood adversity in adolescent BPD. They have important implications for prevention and early intervention as they highlight the need for specific strategies for involving the family.